2009
DOI: 10.2174/1876823700901010009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Socioeconomic Status on Prevalence of Overweight and Obesity among Children and Adolescents in Urban India

Abstract: Abstract:To determine the prevalence and risk factors of overweight and obesity among the school children aged 8-15 years. A cross sectional design was adopted and 3 schools (2 private and 1 corporation schools) were selected by stratified cluster-sampling technique. Data was collected by interviewer administered method by trained research officers using a pre-tested and validated questionnaire to a total sample of 1193 school children from grades IV to X (i.e.) aged 8 to15 years. Prevalence rates were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 19 publications
5
27
1
Order By: Relevance
“…Similar findings were reported by Bharati DR et al, Thakre SB et al, Sain S et al, Goyal RK et al [8][9][10]14 We also examined an association between diet related determinants like type of diet, intake of soft drinks, sweets, pizza, fruits with obesity. It was found that except type of diet all other factors were significantly associated with obesity among private school children.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar findings were reported by Bharati DR et al, Thakre SB et al, Sain S et al, Goyal RK et al [8][9][10]14 We also examined an association between diet related determinants like type of diet, intake of soft drinks, sweets, pizza, fruits with obesity. It was found that except type of diet all other factors were significantly associated with obesity among private school children.…”
Section: Discussionsupporting
confidence: 75%
“…Tharkar S et al observed that the prevalence of overweight was 12.1% among children and 15.5% in adolescents. 10 Kaur J et al noted a prevalence of obesity of 26.84% in private school girls which is higher than that reported by us. 11 This may be because of difference in the climate of Hyderabad and Ludhiana (Punjab).…”
Section: Discussioncontrasting
confidence: 50%
“…[10,21] Factors that are protective against increasing overweight include time spent in physical activity and hours of sleeping. [10,21] The finding of underweight in rural learners indicates the presence of undernutrition in households and communities. [4] Food insecurity is present in 35% of households, despite SA being a middle-income country.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping in mind the prevalence of obesity in adolescents of urban schools of India and taking 20% as allowable error, sample size of 450 was calculated. 21, 22 The sampling population included urban public schools in Amravati. Boys and girls in the age group of 12 to 17 years were included in the study.…”
Section: Methodsmentioning
confidence: 99%